2021
DOI: 10.1186/s12909-021-02910-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraprofessional workplace learning in postgraduate medical education: a scoping review

Abstract: Background Residents need to be trained across the boundaries of their own specialty to prepare them for collaborative practice. Intraprofessional learning (i.e. between individuals of different disciplines within the same profession) has received little attention in the postgraduate medical education literature, in contrast to the extensive literature on interprofessional learning between individuals of different professions. To address this gap, we performed a scoping review to investigate wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…Undergraduate/postgraduate training programs, however, do not provide formal training in IPC/IPL; therefore, studies on this subject are scarce. 4 , 14 In one of the few studies published on this topic, trainees reported that IPC led to a better understanding of one another's professional roles, responsibilities, and behaviours. They observed that most extraprofessional learning occurs informally in the context of patient care.…”
Section: Introductionmentioning
confidence: 99%
“…Undergraduate/postgraduate training programs, however, do not provide formal training in IPC/IPL; therefore, studies on this subject are scarce. 4 , 14 In one of the few studies published on this topic, trainees reported that IPC led to a better understanding of one another's professional roles, responsibilities, and behaviours. They observed that most extraprofessional learning occurs informally in the context of patient care.…”
Section: Introductionmentioning
confidence: 99%
“…In nursing education, the intent of IPL is for nurses to learn how to work with multiple health workers from different professional backgrounds to deliver the highest quality of care to patients, carers, families and communities [ 2 ]. Intraprofessional learning (IaPL) is the learning that occurs when individuals of two or more disciplines within the same profession collaborate [ 3 , 4 ]. Interprofessional learning and its positive effects are widely described in the literature [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intraprofessional learning (IaPL) is the learning that occurs when individuals of two or more disciplines within the same profession collaborate [ 3 , 4 ]. Interprofessional learning and its positive effects are widely described in the literature [ 3 ]. Whilst IaPL is less well documented in health professional education, it has been reported in some studies, for example, dentistry students and dental hygienists learning collaboratively to deliver team-based care [ 5 , 6 , 7 , 8 , 9 , 10 ], occupational therapy and occupational therapist assistant students learning together [ 11 ], physical therapists and physical therapy assistants collaborating within the classroom [ 12 ] and intraprofessional workplace learning in postgraduate medical education [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primary and secondary care trainees acknowledge the importance of learning about PSCC but mention that explicit education in such collaboration is not provided. They mostly learn informally through interaction in the patient-care context [ 12 , 13 ]. To make such interaction more meaningful and create valuable learning opportunities, postgraduate training programmes should pay more explicit attention to learning about PSCC [ 14 ].…”
Section: Introductionmentioning
confidence: 99%